Lightweight Insulating Geopolymer/Phase-Change Materials Applied Using an Innovative Spray Method - Agnieszka Przybek; Paulina Romańska; Jakub Piątkowski; Michał Łach (Applied Sciences)
Foamed geopolymer materials are increasingly studied due to their inherent fire resistance. To date, these materials have primarily been produced by casting into moulds, with foaming occurring during mixing or within the moulds, shortly before setting. For practical applications, however, it is advantageous to apply these materials directly onto surfaces with complex geometries. Although several techniques for geopolymer spraying have been described in the literature, many exhibit limitations that restrict their practical implementation. This study presents a novel spraying technology developed on a dedicated process line, enabling in situ dosing of the foaming agent immediately before application. The system integrates infrared heating to ensure controlled curing of the geopolymer. This paper outlines the design of the process line and its core functionalities while presenting selected results of material tests conducted on the obtained geopolymer coatings. Tests performed on approximately 200 m2 of surface confirmed the functionality of the process. The thermal conductivity of the sprayed foams was about 0.07 W/m-K. The inclusion of a phase-change material (PCM) in the geopolymers further enhanced their ability to store and regulate thermal energy. The adhesion strength results, consistently exceeding 1 MPa across various substrates (steel, geopolymer, gypsum board), confirmed the practical suitability of the proposed solution. This was also demonstrated by the homogeneous foamed structure obtained.